Applications of Activated Sludge Models - Brdjanovic, Damir (IWA Publishing, 2015)
In 1982 the International Association on Water Pollution Research and Control (IAWPRC), as it was then called, established a Task Group on Mathematical Modelling for Design and Operation of Activated Sludge Processes. The aim of the Task Group was to create a common platform that could be used for the future development of models for COD and N removal with a minimum of complexity. As the collaborative result of the work of several modelling groups, the Activated Sludge Model No. 1 (ASM1) was published in 1987, exactly 25 years ago. The ASM1 can be considered as the reference model, since this model triggered the general acceptance of wastewater treatment modelling, first in the research community and later on also in practice. ASM1 has become a reference for many scientific and practical projects, and has been implemented (in some cases with modifications) in most of the commercial software available for modelling and simulation of plants for N removal. The models have grown more complex over the years, from ASM1, including N removal processes, to ASM2 (and its variations) including P removal processes, and ASM3 that corrects the deficiencies of ASM1 and is based on a metabolic approach to modelling. So far, ASM1 is the most widely applied. Applications of Activated Sludge Models has been prepared in celebration of 25 years of ASM1 and in tribute to the activated sludge modelling pioneer, the late Professor G.v.R. Marrais. It consists of a dozen of practical applications for ASM models to model development, plant optimization, extension, upgrade, retrofit and troubleshooting, carried out by the members of the Delft modelling group over the last two decades.